2014
DOI: 10.3346/jkms.2014.29.7.941
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Brachial-Ankle Pulse Wave Velocity Is Independently Associated with Microalbuminuria in a Rural Population

Abstract: Microalbuminuria is a marker of generalized endothelial dysfunction resulting from arterial stiffness or insulin resistance, and brachial-ankle pulse wave velocity (baPWV) is a good measure of arterial stiffness. We aimed to investigate whether elevated baPWV is independently associated with microalbuminuria. This study included 1,648 individuals aged over 40 who participated in the baseline Multi-Rural Cohort Study conducted in Korean rural communities between 2005 and 2006. Participants were classified into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
2
10
2
Order By: Relevance
“…In addition, the prevalences of hypertension (65.8% in the ABI < 0.9 group and 54.1% in the ABI ≥ 0.9 group) and diabetes mellitus (28.9% in the ABI < 0.9 group and 18.3% in the ABI > 0.9 group) were also higher than in our study, which may also contribute to stiffer arteries. In a study conducted in Korean rural communities with participants aged over 40 years, the median baPWV was 1515 cm/s (interquartile range 1325-1764 cm/s), which is similar to that in the present study [23]. Our findings were consistent with those of another community-based cross-sectional study of 2127 community residents of Han ethnicity in Beijing, China aged 60-95 years [22].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the prevalences of hypertension (65.8% in the ABI < 0.9 group and 54.1% in the ABI ≥ 0.9 group) and diabetes mellitus (28.9% in the ABI < 0.9 group and 18.3% in the ABI > 0.9 group) were also higher than in our study, which may also contribute to stiffer arteries. In a study conducted in Korean rural communities with participants aged over 40 years, the median baPWV was 1515 cm/s (interquartile range 1325-1764 cm/s), which is similar to that in the present study [23]. Our findings were consistent with those of another community-based cross-sectional study of 2127 community residents of Han ethnicity in Beijing, China aged 60-95 years [22].…”
Section: Discussionsupporting
confidence: 90%
“…In a community-based cross-sectional study of people of Han ethnicity aged 60-95 years in Beijing, China, the overall rate of pathological albuminuria was 13.16%; this was higher than the 8.25% reported in our study, which can be attributed to the relatively old age of the study population [22]. In another study of a rural population aged over 40 years in Korea, the prevalence of microalbuminuria was 9.9% [23].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…More importantly, receiver operating characteristic (ROC) curve analysis revealed that the optimum baPWV cut-off for predicting the presence of MAU (20 µg/min) in Type 2 DM was 1700 cm/sec. This study showed that 21.9% of the 424 Type 2 DM patients included had MAU, which is much higher than the rates found in previous Korean studies [26,31]. However, previous Korean studies were conducted on healthy subjects.…”
Section: Discussioncontrasting
confidence: 61%
“…Several authors have concluded baPWV provides a useful means of quantitatively assessing cardiovascular events and diabetic complications [21][22][23], and cross-sectional and longitudinal studies have shown baPWV is independently associated with MAU [24][25][26]. Others have suggested baPWV cut-off values for the prediction of mortality [18] and the development of cardiovascular illnesses [27].…”
Section: Introductionmentioning
confidence: 99%